Penelitian pengaruh penambahan impact modifier terhadap sifat ketahanan pukul kompon acuan sepatu - Supraptiningsih, Supraptiningsih; Sayekti, Titien (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 1994)
The aim of this research is to find the type and optimum total of impact modifier of compound PVC for last making. It has three variations, these are total plasticizer DOP, type and total of impact modifier. The optimum PVC compounds is achived by the PVC compound which using DOP 35 phr and 2 phr impact modifier ABS has value of impact resistance 10.2840 kg cm/cm and hardness 60.67 shore D.